The Legal Framework of Duress and its Impact on Criminal Responsibility: A Fundamental Study in Libyan Legislation - Mustafa Masoud Abraheem Abouloasim (Journal of Scientific and Human Dimensions, 2026)
This research examines the legal framework of duress as a primary cause for the preclusion of criminal responsibility within the context of modern legal systems and Libyan legislation. It explores how duress negates the element of free will, thereby affecting the psychological component of a crime. The study analyzes the distinction between physical and moral compulsion, emphasizing the conditions required for duress to be legally recognized, such as the presence of an imminent and grave danger. By reviewing judicial principles and legislative texts, the research highlights the balance between upholding the rule of law and recognizing human vulnerability under pressure. The findings suggest a need for precise judicial interpretation to ensure that the defense of duress is not misused while protecting individuals who are forced into criminal acts against their will.